Electrical Impedance Tomography (EIT) system for monitoring transport processes in industrial installations - Asendrych, Dariusz (Instal, 2025)
Monitoring of transport processes in industrial installations is of crucial importance to avoid problems in process maintenance and to meet the technological requirements. Among various techniques, Electrical Impedance Tomography (EIT) can be considered an efficient tool to diagnose process conditions. It may find its application in the gas and oil industry, food processing, solids transport and many others. It has been proven to be an effective tool in investigating sedimenting particulate flows, fibre suspensions and bubbly flows. As for EIT advantages, one can mention relatively low cost, safety of use and portability.The EIT system is being developed at the Institute of Thermal Machinery, Częstochowa University of Technology. The system is equipped with 32 titanium electrodes mounted in a 25-cm column wall. The voltages collected by the NI-based and LabView-controlled acquisition system are processed numerically to reconstruct the conductivity distribution. The tests of the EIT system have been made using simple configurations. The EIT proved its usefulness for the investigation of multiphase flow systems. However, the system can be easily adapted to many other applications and serve as a powerful tool supporting process monitoring.
Keywords: Electrical Impedance Tomography; finite element method; multiphase flows; online monitoring system